2022
DOI: 10.1002/wsb.1264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fire on prenesting movements of wild turkeys in Arkansas

Abstract: The restoration of historic disturbance regimes is an increasingly common management strategy to conserve disturbance‐dependent communities and species, and enhance resilience of ecosystems to climate change or plant and animal invasions. However, the reintroduction of frequent and wide‐scale disturbance may have unexpected consequences on species that are accustomed to an environment absent of frequent disturbance. Implementation of frequent prescribed fire for community restoration has coincided with populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Empirical evidence of the kills and direct consumptions of wild turkeys by coyotes is intuitively required to support the impacts of coyote populations on wild turkey populations. Studies have ascribed predation by canids, including coyotes, as a major mortality cause of wild turkeys in Arkansas, Kansas, and Missouri, USA (Holdstock et al, 2006; Thogmartin & Schaeffer, 2000; Vangilder & Kurzejeski, 1995), consistent with our findings of the negative impacts of increased coyote abundance on wild turkey population in Mississippi. Wild turkeys were also present in the diet of coyotes, constituting <4% of the diet, in Alabama, Arkansas, Florida, and Mississippi of the Southeastern US (Wagner & Hill, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Empirical evidence of the kills and direct consumptions of wild turkeys by coyotes is intuitively required to support the impacts of coyote populations on wild turkey populations. Studies have ascribed predation by canids, including coyotes, as a major mortality cause of wild turkeys in Arkansas, Kansas, and Missouri, USA (Holdstock et al, 2006; Thogmartin & Schaeffer, 2000; Vangilder & Kurzejeski, 1995), consistent with our findings of the negative impacts of increased coyote abundance on wild turkey population in Mississippi. Wild turkeys were also present in the diet of coyotes, constituting <4% of the diet, in Alabama, Arkansas, Florida, and Mississippi of the Southeastern US (Wagner & Hill, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…In the second case study, we examined potential predator-prey interactions and movement patterns in bobcat and wild turkey while assuming Poisson observations to allow the count to be smaller (false negative) or larger (double counting) than the true abundance. The bobcat is a generalist species that prey not only on a variety of mammalian species such as snowshoe hare Lepus americanus and porcupines Erethizon dorsatum but also prey on wild turkeys (Beasom & Moore, 1977;Litvaitis et al, 1986;Pollack, 1951;Thogmartin & Schaeffer, 2000), indicating a potential top-down process but not necessarily a bottom-up process in our study system. Studies also have found differentiated habitat preference of bobcats and wild F I G U R E 1 Violin plots showing the relative bias based on the posterior distributions of parameters in a competition system (left two columns) or a predator-prey system (right two columns) with binomial or Poisson observations.…”
Section: Case Study 2: Predator-prey Interactions Between Bobcat and ...mentioning
confidence: 92%
“…We had to restrict the mean population growth rate to 1 due to the short time period of this study, but it is encouraging to see that the model could reveal the effect of bobcat abundance on the spatial variation of wild turkey population growth. Bobcats have been documented as predator of wild turkeys (Litvaitis et al, 1986), including during winter (Thogmartin & Schaeffer, 2000), thus, the top-down process suggests that abundance of bobcat may have contributed to declines in wild turkey abundance. Our results suggest that bobcat abundance could be one factor limiting continued growth of the wild turkey population in New York.…”
Section: Capability Of Dynamic N-mixture Modelsmentioning
confidence: 99%
“…Evidence such as tracks, feces, fur, carcass caching, and bite marks on the transmitter identified the mortality as mammalian predation. Sharp puncture wounds accompanied by removal of the head and neck region from the carcass, as well as presence of raptor feathers at the kill site, were characteristic of avian predation events (Miller and Leopold 1992, Thogmartin and Schaeffer 2000, Lehman et al 2007).…”
Section: Methodsmentioning
confidence: 99%